Guidelines for academic administration to promote professional competency of students in educational institutions Under the Suphanburi Provincial Vocational Education Office - khaoto, Surachet; Niyamabha, Achara (Mahachula Academic Journal, 2024)
The objectives of this research are (1) to study the current condition; desirable condition and the essential needs of academic administration guidelines to promote student professional competency in educational institutions. Under the Suphanburi Provincial Vocational Education Office (2) To propose guidelines for academic administration to promote student vocational competency in educational institutions. Under the Suphanburi Provincial Vocational Education Office The research method has 2 steps: Step 1: Study the current condition. desirable condition and the necessary needs of academic administration to promote the professional competency of students in educational institutions. The sample group was school administrators and teachers. Under the Suphanburi Provincial Vocational Education Office, there were 314 people. The research instrument was a questionnaire with a reliability value of the current condition of 0.93 and the desired condition of 0.96. Data were analyzed using mean and standard deviation. and the index of essential needs, and step 2 presents guidelines for academic administration to promote student professional competency in educational institutions. The main informants were 4 educational institution administrators and 1 academician, 1 full-time lecturer in educational administration, and 1 research lecturer, which were obtained through the purposive selection method. The research instrument used was a semi-structured interview. and analyzed the data by means of content analysis. The results were (1) The current state of academic administration guidelines to promote learner professional competency in educational institutions. Under the Suphanburi Provincial Vocational Education Office Overall, every aspect has an average level at a moderate level. desirable condition Overall, every aspect was at the highest average level. and the first three essential needs include curriculum development In terms of teaching and learning management and measurement and evaluation (2) guidelines for academic administration to promote student professional competency in educational institutions Under the Suphanburi Provincial Vocational Education Office Consists of a total of 40 action items, considering the first 3 essential needs in 3 areas, namely, Side 1: curriculum development, 9 action items, such as administrators creating a manual specifying procedures for developing the curriculum of educational institutions; Side 2: Organize teaching and learning with 8 practical items, such as teachers encouraging students to use the learning process by themselves according to their aptitude in professional competency, and the third area of measurement and evaluation, 6 practical items, such as teachers having appropriate principles for making decisions in selecting Methods for measurement and evaluation to develop students' professional competencies. Keywords: Promoting; Academic Affairs Management; professional competencies